Cosmic Ray Spallation in Radio-Quiet Active Galactic Nuclei: A Case Study of NGC 4051 - Turner, T; Miller, L (2009)
We investigate conditions for and consequences of spallation in radio-quiet Seyfert galaxies. The work is motivated by the recent discovery of significant line emission at 5.44 keV in Suzaku data from NGC 4051. The energy of the new line suggests an identification as Cr I Ka emission, however the line is much stronger than would be expected from material with cosmic abundances, leading to a suggestion of enhancement owing to nuclear spallation of Fe by low energy cosmic rays from the active nucleus. We find that the highest abundance enhancements are likely to take place in gas out of the plane of the accretion disk and that timescales for spallation could be as short as a few years. The suggestion of a strong nuclear flux of cosmic rays in a radio-quiet Seyfert galaxy is of particular interest in light of the recent suggestion from Pierre Auger Observatory data that ultra-high-energy cosmic rays may originate in such sources.